Improving Student Learning Outcomes Through Demonstration Methods in Heat Controlling Properties of Science Materials for Class VI MI Muhammadiyah Padangjaya Academic Year 2013/2014 - Siti Nasihatul Mukaromah (UM Purwokerto Press, 2023)
Learning is basically an activity that should be fun for students. Because they will get new knowledge that is useful for themselves. Therefore a teacher needs to be skilled in making the atmosphere of the learning process more meaningful and not boring in all subjects. This study aims to determine the steps of applying the demonstration method and student learning outcomes in science learning on heat-conducting properties of class VI MI Muhammadiyah Padangjaya students. The research was conducted in class VI, which consisted of 20 students, consisting of 8 female students and 12 male students. The design used in this research is using classroom action research (CAR) using two cycles. Methods of collecting observations, tests, and interviews. The instruments used were student activity observation sheets, student learning outcomes assessment sheets, and interview questions. The data was obtained using qualitative analysis and quantitative description. The demonstration method can improve science learning outcomes about heat conducting properties in class VI MI Muhammadiyah Padangjaya students. This can be proven by the results of the research showing that the passing rate of student learning outcomes increased from 69.25 % to 78.75%. The conclusion of this study is that the demonstration method can improve student learning outcomes in science learning on heat-conducting properties in class VI MI Muhammadiyah Padangjaya.